Asuhan Keperawatan pada Anak dengan Gangguan Nutrisi Akibat Kanker melalui Pendekatan Model Adaptasi Roy: Nursing Care for Children with Nutritional Disorders Due to Cancer Through Roy's Adaptation Model Approach - Muhsinin; Deswita (NERS Jurnal Keperawatan, 2012)
Cancer in children has increased over the years, including in Indonesia. This literature review provides an overview of the application of the Roy Adaptation Model nursing care to children with cancer with nutrition problems. The role of nurses needed in the application of the Roy Adaptation Model provides nursing care to children and families in order to behave adaptively during treatment of cancer. Roy Adaptation Model is based on the consideration that children with cancer require special handling and complicated chemotherapy that affects the digestive system disorders that cause malnutrition. The family needs adaptation to care and treat their children continuously. The nursing diagnosis is the main nutritional needs less interference than the body needs. Nursing interventions are given in the form of providing motivation and support to clients and families, health education, monitoring and anthropometric examination, and dental and oral care. Other activities to achieve optimal nursing care include family education regarding the care and treatment of cancer.